PENDAMPINGAN PROGRAM QA/QC RADIOLOGI DI INSTALASI RADIOLOGI RSI KENDAL - Andriani, Intan; Budiwati, Trisna; Rosidah, Siti (Universitas Widya Husada Semarang, 2022)
Quality control is one part the program of quality assuranceor quality quality assurancewhich aims to carry out technical monitoring and maintenance so as not to reduce the quality of the resulting image and is alasi part of a quality assurance program related to instruments or aircraft use and equipment.The radiology Instalation of Kendal Islamic Hospital has several imaging modalities, including CTScan, Conventional radiography and ultrasonography. The conventional radiography aircraft owned by the hospital has the listem brand with a capacity of 150 mA. The last test of the exposure rate on the aircraft was carried out in August 2021 when the aircraft underwent repairs. The community service team wants to provide solutions to the problems experienced by partners, namely by providing conformity test services related to the rate of exposure to X-ray tube leaks. In addition, providing motivation to partners to routinely carry out conformity test so that the aircraft remains safe when used. The method of implementing the service is to carry out a conformity test procesure for X-ray tube leakage based on KMK No. 1250 regarding quality controlThe result of the measurement of the rate of radiation exposure at the patient’s entrance and exit were 34,12 mR/week. According to IAEA Safety Report No. 47, Radiation exposure occupied by radiation workers should not exceed 2,5 mR/hour (for controlled areas), while for theh general public is should not exceed 0,25 mR/hours (for uncontrolled areas).Keyword : exposure rate, examination room leak, RSI Kendal